1984
DOI: 10.3109/10826088409057179
|View full text |Cite
|
Sign up to set email alerts
|

Paraprofessional Versus Professional Drug Abuse Counselors: Attitudes and Expectations of the Counselors and Their Clients

Abstract: Three groups of methadone maintenance and drug-free outpatient counselors, ex-addict paraprofessionals (EXAs), non-ex-addict paraprofessionals (NEAs), and degreed professional counselors (PROs), were contrasted in terms of their views of drug abuse and drug treatment, their attitudes toward and expectations for their clients, and in terms of their clients' attitudes toward them. Across groups, counselors agreed on the major cause of drug abuse, the critical factor in treatment, the definition of treatment succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…They mention that counselors in recovery act as a resource person for other non-past addicted staff lend street credibility to the program and act as a role model, helping to make it more acceptable to suspicious clients [13][14][15][16][17]. To substantiate these observations, studies report that when compared to the non-addict, patients surveyed found that the ex-addict counsellor contributed more helpful opinions and guidance [18,19], developed better relationships and understanding [6,20] and were able to spot abuse much better [21]. There are however two survey-based studies that found no difference between the ex-addict and non-ex-addict when patients were asked to rate performance [22], and perception of empathy [23].…”
Section: Literature Reviewmentioning
confidence: 89%
See 2 more Smart Citations
“…They mention that counselors in recovery act as a resource person for other non-past addicted staff lend street credibility to the program and act as a role model, helping to make it more acceptable to suspicious clients [13][14][15][16][17]. To substantiate these observations, studies report that when compared to the non-addict, patients surveyed found that the ex-addict counsellor contributed more helpful opinions and guidance [18,19], developed better relationships and understanding [6,20] and were able to spot abuse much better [21]. There are however two survey-based studies that found no difference between the ex-addict and non-ex-addict when patients were asked to rate performance [22], and perception of empathy [23].…”
Section: Literature Reviewmentioning
confidence: 89%
“…One of the common areas quantitatively researched was the education status of the paraprofessional, with studies reporting that the person in recovery enters the field at an older age and has less education than the non-recovering counsellor [3,[4][5][6][7]. Other quantitative studies have found that compared to the non-recovering counsellor, recovering counsellors are resistant to new learning [8,9], are overcommitted to one treatment modality due a personal loyalty to the 12 -step approach [7,10,11], and operate from a limited frame of reference because they view all clients in terms of being addicted or not, which might lead to over diagnosis [12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To date there is no research on whether ex-addict counsellors are able to develop more supportive therapeutic relationships with their clients. However, there is related research which indicates that there may well be differences between ex-addict and non-addict counsellors that may affect the development of the relationship (LoSciuto, Aiken, Ausetts and Brown 1984). From personal experience, it seems that many UK agencies tend to operate a system of matching female clients to female counsellors, but that such matching is not usually offered to male clients.…”
Section: Introductionmentioning
confidence: 99%
“…Given that some administrators in recovery made a career change later in their life and may have less formal education than counselors who are not in recovery (Doukas & Cullen, 2011;LoSciuto et al, 1984), professional development could focus on self-care and healthy professional boundaries and on enhancing counselors' clinical competence by adhering to the professional standards and recommendations of addiction counseling.…”
Section: Discussionmentioning
confidence: 98%